Cardiovascular and Kidney Outcomes After Systemic Treatment for Plaque Psoriasis: A Systematic Review and Network Meta-analysis - Ao Shi; Yuan Shu; Joe El Haddad; Shuqin Wu; Karen Smayra; Shivon Mirza Sudesh; Mohammed Majd Mourad; Armin Farzad; Nathanael Yap; Efstathia Andrikopoulou; Qi Liu; Pengyang Li; et al. (Dermatology and Therapy)
Abstract Introduction Systemic immunomodulatory treatments may affect cardiovascular and renal outcomes in patients with chronic plaque psoriasis. We conducted a network meta-analysis (NMA) to compare these outcomes of systemic treatments for plaque psoriasis. Methods Databases were searched from inception through June 1, 2023. We conducted duplicate study selection, data extraction, bias assessment risk, and NMA evidence certainty assessment and analyses. Outcomes included proportion of participants achieving Psoriasis Area and Severity Index (PASI) 75 and/or 90 and those with (1) total cardiovascular events, (2) major adverse cardiovascular events (MACE), (3) other cardiovascular events, and (4) total renal events. Results We included 68 randomized clinical trials (n = 34,414 patients). Compared with placebo, bimekizumab (odds ratio [OR] 101.12, 95% confidence interval [CI] 34.26–301.46, surface under the cumulative ranking curve [SUCRA] 27, high certainty) was the top treatment demonstrating better PASI 75 and had reduced total cardiovascular events (OR 0.06, 95% CI 0–0.80, SUCRA 89, moderate certainty). Ixekizumab (OR 86.92, 95% CI 39.06–199.66, SUCRA 15, high certainty) showed better PASI 90 rates but was associated with increased MACE over placebo (OR 3.26, 95% CI 1.26–9.31, SUCRA 26, high certainty) and bimekizumab (OR 31.92, 95% CI 2.01, 1123.25), moderate certainty). Renal outcomes were similar among groups. Conclusion Bimekizumab showed better therapeutic efficacy scores and safety profile than other agents. Ixekizumab may increase cardiovascular risk and should be used with caution. Reliable long-term safety data of the treatments analyzed here require assessing non-randomized studies and examining postmarketing reports from regulatory agencies. Trial Registration PROSPERO (CRD42022381489). Graphical Abstract